Partial migration of Brolgas (Antigone rubicunda) within a restricted range is revealed by GPS tracking. (2nd January 2022) - Veltheim, Inka; Cook, Simon; McCarthy, Michael A.; Palmer, Grant C.; Hill, F. A. Richard
ABSTRACT: No quantitative information exists on the movement patterns of Brolga, Antigone rubicunda (Gruidae) although the species is considered to undertake seasonal movements between breeding and non-breeding areas, and has been also described as both non-migratory and partly migratory. Information on this species' movement behaviour is required to understand its basic ecology and inform conservation management across its range. Thus, we sought to investigate whether Brolgas in southern Australia undertake seasonal movements, to define routes travelled by individuals, and to clarify the species' migratory status. Here, for the first time for this species, we quantified the distances travelled, timing of movements between breeding and non-breeding areas, and individual-level differences in movement patterns. We deployed GPS transmitters on five adults, six juvenile and 12 unfledged 6–9 week chicks in Victoria, Australia. Individuals were monitored for 71–646 days. These Brolgas showed partial migratory behaviour, with the south-west Victorian population including resident and migrating individuals, moving 6–30 km and 96–111 km between breeding and non-breeding areas respectively and some remaining resident throughout the year. Brolgas moved 1.6 km from roost to foraging areas on average throughout the year, the majority (95%) of these movements were within 5.2 km and overall Brolgas moved shortest distances during the non-breeding season. We discuss the main potential drivers for these movement patterns. These findings may assist local conservation planning and add to our understanding of Australian waterbird movements more broadly.